Immaturity of Visual Fixations in Dyslexic Children - Tiadi, Aimé; Gérard, Christophe-Loïc; Peyre, Hugo; Bui-Quoc, Emmanuel; Bucci, Maria Pia (Frontiers in Human Neuroscience, 2016)
To our knowledge, behavioral studies recording visual fixations abilities in dyslexic children are scarce. The object of this paper is to explore further the visual fixation ability in dyslexics compared to chronological age-matched and reading age-matched non-dyslexic children. Fifty-five dyslexic children from 7 to 14 years old, fifty-five chronological age-matched non-dyslexic children and fifty-five reading age-matched non-dyslexic children participated to this study. Eye movements from both eyes were recorded horizontally and vertically by a video-oculography system (EyeBrain® T2). The fixation task consisted in fixating a white-filled circle appearing in the centre of the screen for 30 seconds. Results showed that dyslexic children produced a significantly higher number of unwanted saccades than both groups of non-dyslexic children. Moreover, the number of unwanted saccades significantly decreased with age in both groups of non-dyslexic children, but not in dyslexics. Furthermore, dyslexics made more saccades during the last 15 sec of fixation period with respect to both groups of non-dyslexic children. Such poor visual fixation capability in dyslexic children could be due to impaired attention abilities, as well as to an immaturity of the cortical areas controlling the fixation system.